Don DeLillo : The Physics of Language - Cowart, David, 1947- (Book collections on Project MUSE., 2003)
"Don DeLillo, author of twelve novels and winner of the National Book Award, the PEN/Faulkner Award, the William Dean Howells Medal, and the Jerusalem Prize, has begun to rival Thomas Pynchon as the definitive postmodern novelist. Always thought-provoking and occasionally controversial, DeLillo has become the voice of the bimillennial moment. Charting DeLillo's emergence as a contemporary novelist of major stature, David Cowart discusses each of DeLillo's twelve novels, including his most recent work, The Body Artist (2001). Rejecting the idea that DeLillo lacks affinities across the cultural spectrum, Cowart argues that DeLillo's work invites comparison with that of wide range of antecedents, including Dunbar, Whitman, Wittgenstein, Heidegger, Freud, Lacan, Derrida, Hemingway, Joyce, Rilke, and Eliot. At the same time, Cowart explores the ways in which DeLillo's art anticipates, parallels, and contests ideas that have become the common currency of poststructuralist theory. The major site of DeLillo's engagement with postmodernism, Cowart argues, is language, which DeLillo represents as more mysterious--numinous even--than current theory allows. For DeLillo, language remains what Cowart calls "the ground of all making." Don DeLillo: The Physics of Language is a provocative investigation of the most compelling issues of contemporary fiction."--Project Muse.